COMMERCIAL STRATEGIES FOR ENHANCING FOOD SECURITY: THE INTERSECTION OF NUTRITIONAL SCIENCE AND MARKET ECONOMICS (International Journal of Food and Nutritional Sciences, 2021)
Abstract: Food security is a critical global challenge influenced by both nutritional science and market economics. This paper explores commercial strategies designed to enhance food security by integrating insights from nutritional science with market-driven approaches. By analyzing the intersection of these fields, the study identifies key strategies for improving food access, quality, and sustainability. We examine how market dynamics, including supply chain management and pricing strategies, can be aligned with nutritional goals to create more resilient and equitable food systems. The paper discusses innovative commercial practices, such as value-added products, sustainable sourcing, and strategic partnerships, that contribute to food security while addressing economic considerations. Through a review of case studies and empirical data, we highlight successful models and propose a framework for leveraging commercial strategies to achieve better food security outcomes.